ANALISIS IRWEEMIENTASI MEBIJBKAN DANA ALOKASI JCHUSUS @AK) DP DINAS PENDIDIKAN PEMVDA D-AN OEAKRAGA PERTEMNTAH KOTA MUPANG - , Magdalena P. Manafe, S.Sos ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The title of this study is the Implementation of Specific Fund Allocation (SFA) Policy in Office of Education, Youth and Sport, Municipal Government of Kupang. Purposes of the study are to compare between the Allocation of SFA in Local Budget and its realization, evaluate the role of SFA in Human Development Index, and identify factors leading problems in the implementation of SFA. Descriptive qualitative method was used in the study with a multiple linear regression as an analysis technique. The study used primary and secondary data collected by using questionnaire and interview techniques. Result of the study indicates that the SFA policy could not be implemented effectively yet. In view of the SFA regulation aspect, a significant effect of the implementation of SFA policy was that all the regulations were issued by Central Government and no regulation at a local level was used as a reference for SFA. In view of funding aspect, most funding sources were fiom National Budget, where despite the increased number of fund, it was not sufficient, so fund fiom General Fund Allocation (GFA) should be allocated for equilibrium. In view of inspection aspect, the process was weak both int emally where local inspection board did not perform its function well and externally where the Finance Inspection Board of the Republic of Indonesia just done inspection once during the implementation of SFA policy. Finally, in view of responsibility aspect, the implementation was not in accordance with the existing mechanism. Result of the study indicates also that the implementation of SFA policy was one of the efforts of improving its effectiveness and in practice it successfully achieved the objective. The implementation of SFA policy was influenced by four variables, namely, regulation, funding, inspection, and responsibility. Although all the variables tended to retard the successful implementation, it is still possible to be successful if improvement is done, mainly in relation to the aspects of specific activities funded by the SFA.